2007
DOI: 10.3141/1999-07
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Reductions in Freeway Capacity due to Incidents in Microscopic Simulation Models

Abstract: Modeling the impacts of incidents on traffic flow operations is essential for the use of simulation programs to evaluate incident management alternatives. In particular, these programs must be able to model correctly the reductions in highway capacity that are due to incidents and the lane-changing behaviors of drivers ahead of incident locations. Although simulation models have been used for evaluating incident impacts, the abilities of these programs to model incidents have not been adequately assessed. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…(12) Juxtaposing the approach and the results of this study with other studies are quite challenging, since most incident modeling studies utilizing microscopic traffic simulation directed only on controlled freeway lane closure, for example, work zones [25]. Another study by [26] aimed at simulating incidents-induced capacity reduction but did not investigate the SW speeds and queue length due to the incident.…”
Section: Resultsmentioning
confidence: 99%
“…(12) Juxtaposing the approach and the results of this study with other studies are quite challenging, since most incident modeling studies utilizing microscopic traffic simulation directed only on controlled freeway lane closure, for example, work zones [25]. Another study by [26] aimed at simulating incidents-induced capacity reduction but did not investigate the SW speeds and queue length due to the incident.…”
Section: Resultsmentioning
confidence: 99%
“…The incident-reduced capacity and normal capacity cannot be directly defined in microscopic simulators. By measuring traffic throughput from several traffic counters under congestion condition as capacity, Hadi et al (2007) simulated reduced capacities in several popular microscopic simulators and found that when using default parameter settings, they are lower than the reduction factors reported in the HCM 2000 for a one-lane-blocking incident on a three-lane freeway segment. Therefore, for this study, a simple calibration is done to match the specified capacity in HCM 2000.…”
Section: Capacity Reduction Due To An Incidentmentioning
confidence: 95%
“…A number of studies utilised microscopic simulation to model traffic incidents and the impact of their characteristics (Dia et al, 2006;Chou and MillerHooks, 2011;Jeihani et al, 2011;Martin et al, 2011a). Hadi et al (2007) compared the capabilities of three microscopic simulation models.…”
Section: Simulation Modelsmentioning
confidence: 99%